1995
DOI: 10.1063/1.113397
|View full text |Cite
|
Sign up to set email alerts
|

Near field probe microscopy of porous silicon: Observation of spectral shifts in photoluminescence of small particles

Abstract: Imaging of topography and locally induced photoluminescence of anodically etched porous silicon is performed using a force regulated near field scanning optical microscope. The photoluminescence signal on as-prepared wafers shows strong evidence for inherent, rather than purely geometrically induced, variations. Images of small particles display distributions of regions of relatively strong luminescence on the 100 nm lateral scale. Highly localized photoluminescence spectra obtained on these particles show spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In a series of recent publications, we have utilized near-field scanning optical microscopy (NSOM) to study the long, flexible, fluorescent fibers observed in thin films produced from aqueous mixtures of the pseudo-isocyanine dye (PIC), 1,1‘-diethyl-2,2‘-cyanine iodide, and the anionic polymer poly(vinyl sulfate) (PVS). NSOM is a new form of scanned-probe microscopy which utilizes light as the imaging mechanism and provides subwavelength spatial resolution in visible-light imaging and spectroscopy experiments on materials surfaces. We utilized NSOM in our previous publications to directly study the morphological and electronic properties of the PIC/PVS fibers spin-coated onto fused-quartz substrates. In our first publication, we showed that the fluorescent nature of the fibers resulted from the self-assembly of a well-ordered, homogeneous molecular arrangement of PIC within the fibers .…”
Section: Introductionmentioning
confidence: 99%
“…In a series of recent publications, we have utilized near-field scanning optical microscopy (NSOM) to study the long, flexible, fluorescent fibers observed in thin films produced from aqueous mixtures of the pseudo-isocyanine dye (PIC), 1,1‘-diethyl-2,2‘-cyanine iodide, and the anionic polymer poly(vinyl sulfate) (PVS). NSOM is a new form of scanned-probe microscopy which utilizes light as the imaging mechanism and provides subwavelength spatial resolution in visible-light imaging and spectroscopy experiments on materials surfaces. We utilized NSOM in our previous publications to directly study the morphological and electronic properties of the PIC/PVS fibers spin-coated onto fused-quartz substrates. In our first publication, we showed that the fluorescent nature of the fibers resulted from the self-assembly of a well-ordered, homogeneous molecular arrangement of PIC within the fibers .…”
Section: Introductionmentioning
confidence: 99%
“…These methods are widely applied to study individual NCs of III-V and II-VI semiconductors 3 but have only scarcely been used to study light emission from silicon NCs ͑Si NCs͒. 4,5 Two main difficulties are the low emission rate from the Si NC ͑long radiation lifetime resulting from the indirect transition͒ and the complicated preparation of diluted and well-defined systems of Si NCs. Recently, the Buratto group reported PL studies of dispersed single porous-Si grains.…”
mentioning
confidence: 99%
“…In order to separate the topographical effect from the fluorescence signal, the effect of the particle shape must be considered (Rogers et al ., 1995). The effect of the particle shape is important when the electric field distribution in the particle has some obvious feature, for example the whispering gallery mode in a spherical particle.…”
Section: Resultsmentioning
confidence: 99%